A Multicenter Retrospective Study of Frameless Robotic Radiosurgery for Intracranial Arteriovenous Malformation - Oermann, Eric K. (Frontiers Media S.A., 2014)
Introduction: CT-guided, frameless radiosurgery is an alternative treatment to traditional catheter-angiography targeted, frame-based methods for intracranial arteriovenous malformations (AVMs). Despite the widespread use of frameless radiosurgery for treating intracranial tumors, its use for treating AVM is not-well described.